Estrutura de governança e capacidade de adequação ao aparato legal ambiental : um estudo em destilarias do Estado do Paraná - Augusto, Cleiciele Albuquerque (2011)
In recent years, the alcohol sector has been identified as a driver of national development, considering the economic benefits it has provided. Moreover, it has been criticized by the degradation that activities related to the production of alcohol can bring to the environment. Whereas ethanol production is not just a segment, since there is an interdependency relationship between producers and processors, a problem of coordination and governance arises. This coordination is achieved through governance structures that are able to minimize the transaction costs involved. Traditionally, governance structures have been studied by Transaction Cost Economics (TCE). However, more recent studies have sought additional aspects of the Resource Based View (RBV) approach to understand the configuration of these structures in order to answer some limitations of ECT. Thus, the goal in this work is to address these limitations in order to understand how the governance structures, set up by different resources and capabilities, may affect the response to stimuli imposed by environmental legal apparatus, in the producers and processors relations, in distilleries located in the state of Parana. For this, a qualitative and descriptive research, with cross-sectional and longitudinal perspective, was conducted. The study involved semi-structured interviews with five managers and agricultural producers engaged in distilleries located in the state of Parana. The results showed that the major environmental laws that affect the relationship between producers and processors, demanding answer, are related to registration of permanent and legal reserves and burned performance. Regarding the governance structures employed by the Paraná?s distillery, vertical integration and market are usually not used. In this sense, it was noticed a strong tendency towards the use of contracts that give more uprighted, mostly through partnership-type lease. The second choice of organizational arrangement has been the agricultural partnership contract, followed by the supply contract. In relation to strategic resources and capabilities that can generate competitive advantage for the distilleries, the contracted property location and average distance were the most frequent. Besides these, other strategic resources such as capacity expansion (due to soil fertility, abundance of mechanized areas and absence of competitors), transparency, reputation, loyalty, tradition and knowledge were also identified. Regarding response capability, the lease type partnership contract was identified as the most appropriate to optimize the care of the distilleries to the environmental laws because of the obtained full control over productive process. The agricultural partnership and supply contracts may require more time to meet legal requirements, since they involve the coordination of the relationship of the distillery with its contractors. Complementarity is ratified, in this way, from the consideration that the distilleries internal resources and capabilities such as location, distance, knowledge, among others, influence the choice of more vertically integrated governance structures. These, in turn, are chosen to explore, protect and gain competitive advantage obtained through the control over those resources.